Investigation of some properties of a composite biomaterial based on betulin treat infected wounds and burns - Fedorishin, Dmitriy A.; Bakibaev, Abdigali A.; Lyapunova, Maria V.; Takibayeva, Altynaray T.; Demets, Olga V.; Kurzina, Irina A.; Mamaeva, Elena А.; Aliyeva, Madina R. (Вестник Томского государственного университета. Химия)
An urgent problem of modern medicine is the problem of treatment of infected wounds, which is associated with the prevalence of wounds of various etiolo-gies, purulent complications, high mortality, and high material costs of treatment. For the treatment of wounds most often used local effects of drugs, in particular, use a variety of coatings and dressings. Types of these dressings are quite diverse. They can be created on the basis of bioresorbable materials, contain other therapeutic substances such as enzymes, anesthetics, antibiotics in order to have a complex effect on the wound healing process. The choice of optimal local wound coatings or their effective combinations with physiotherapeutic methods of treatment of local superficial and deep wounds and prevention of wound infection remains an unsolved problem. In this regard, the creation of new wound healing preparations and wound coatings based on them seems to be very relevant. At the moment, there are many biologically active substances suitable for the therapy of wounds and burns. These substances can have a variety of origins - both synthetic and natural. Recently, the attention of specialists to drugs of natural origin is constantly growing. Interest in the use of such drugs is justified by their high efficiency, the lack of the need for complex synthesis, a wide range of pharmacological activity, as well as the possibility of using them for a long time without complications and side effects. The specific weight and volume of production of medicines obtained by synthetic transfor-mations of substances extracted from wild and cultivated plants is increasing world-wide. Substances of plant origin are now increasingly being used in medical products for a wide range of purposes. One of such substances are derivatives of natural pentacyclic triterpenoid betulin extracted from birch bark. Betulin and its derivatives have high biological activity. This substance and its derivatives exhibit a complex of biologically active properties such as wound healing, antibacterial, antitumor, hypolipidemic, hepatoprotective, antiviral and others. Betulin, overcoming resistance, induces apoptosis of malignized cells in various human cancers. It should also be noted that sufficient raw material base and biological activity of betulin put it in a number of valuable natural sources for use both in the native state and in the form of various transformation products, which makes it relevant to develop drugs based on it.